The Role of Entrepreneurial Leadership in Enhance Organizational Agility in Telecommunication Sector - Avan Ibrahim; Wirya Najm Rashid (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The new leadership role in competitive globalization focuses on developing and integrating entrepreneurial activity into existing organizational systems. However, there is a lack of research into how entrepreneurial leadership can influence organizational agility in the telecommunications sector in Kurdistan Iraq. The aim of this research is to find out the impact of entrepreneurial leadership on organizational agility, data collected through a quantitative methodology research design from (143) managers in an Asia cell company in Sulemani City, Iraq. using SPSS, V.21. The correlation results of the research showed a direct relationship between entrepreneurial leadership and organizational agility. In addition, entrepreneurial leadership has a decisive influence on the mobility of the organization. The regression results of the research show the importance of entrepreneurial leadership in increasing organizational agility. Finally, this research suggests that future research may explore the concept in a different context.